Gauteng cornea and eye bank registry: a report on corneal grafts done between January 1998 and December 2005 - Makgotloe, Aubrey Zacharia (My University, 2010)
Aim: To describe and analyse donor demographics; source, utilisation and distribution of corneal tissue procured by the Gauteng cornea and eye bank (GCEB). To further establish the indications for penetrating keratoplasty done by private ophthalmologists in Johannesburg. Methods: A retrospective study of the records from the GCEB for the 8 year period from 1998 to 2005. An analysis for each year was done in respect of donor demographics; corneal donor tissue source and distribution. Records from selected corneal surgeons in private practice in Johannesburg were analysed for indications for penetrating keratoplasty. Results: During the study period, 2504 corneas were retrieved from 1252 donors. The average number of donors per year was 157 (Standard deviation: 20.01). There was a statistically significant increase in the number of donors over the study period (B-coefficient = 6.40, standard error=2, 07, p-value=0.02). Majority of donors were males (68.6%). The mean age of donors was 40.4 years (Standard deviation: 15.97) and ranged from 3 months to 78 years. Whites were in overwhelming majority compared to other races, accounting for 96% (number=1205), followed by Blacks 2% (number=24), Asians 1% (number=18) and Coloureds <1% (number=5). The proportion of donated corneas used for transplantation (corneal utilisation rate) averaged 87%. This rate showed a significant decline over the period studied (Bcoefficient= -1.76, standard error=0.48, p-value=0.01). The commonest reason for discarding corneas was damaged corneas (36%), followed by Human immunodeficiency virus infection (18%) and inconclusive blood results (14%). The majority of donated corneas were used in private practices (91%). vi The majority of donors were referred by mortuaries (50%) and private hospitals (37%). The commonest indication for penetrating keratoplasty was keratoconus (46.8%), followed by corneal scarring (27.8%) and pseudophakic bullous keratopathy (10.1%) Conclusions: This analysis shows that the number of donors increased annually over the study period. There were very few Blacks donating corneas in Johannesburg and most of the referrals were from mortuaries and private hospitals. The distribution of corneal tissue in areas served by the Gauteng cornea and eye bank is in favour of private hospitals. Corneal tissue damage and HIV infection were the commonest reasons for discarding corneas. In private practices in Johannesburg, keratoconus was the commonest indication for penetrating keratoplasty, followed by traumatic corneal scarring.
MMed, Ophthalmology, Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: corneal grafts; Johannesburg, Gauteng